Ambulatory Blood Pressure Monitoring in Spinal Cord Injury: Clinical Practicability - Hubli, Michèle; Krassioukov, Andrei V. (Journal of neurotrauma, 2014)
Trauma to the spinal cord often results not only in sensorimotor but also autonomic impairments. The loss of autonomic control over the cardiovascular system can cause profound blood pressure (BP) derangements in subjects with spinal cord injury (SCI) and may therefore lead to increased cardiovascular disease (CVD) risk in this population. The use of ambulatory blood pressure monitoring (ABPM) allows insights into circadian BP profiles, which have been shown to be of good prognostic value for cardiovascular morbidity and mortality in able-bodied subjects. Past studies in SCI subjects using ABPM have shown that alterations in circadian BP patterns are dependent on the spinal lesion level. Tetraplegic subjects with sensorimotor complete lesions have a decreased daytime arterial BP, loss of the physiological nocturnal BP dip, and higher circadian BP variability, including potentially life-threatening hypertensive episodes known as autonomic dysreflexia (AD), compared with paraplegic and able-bodied subjects. The proposed underlying mechanisms of these adverse BP alterations mainly are attributed to a lost or decreased central drive to sympathetic spinal preganglionic neurons controlling the heart and blood vessels. In addition, several maladaptive anatomical changes within the spinal cord and the periphery, as well as the general decrease of physical daily activity in SCI subjects, account for adverse BP changes. ABPM enables the identification of adverse BP profiles and the associated increased risk for CVD in SCI subjects. Concurrently, it also might provide a useful clinical tool to monitor improvements of AD and lost nocturnal dip after appropriate treatments in the SCI population.